Evaluation of Third Degree Football Referees’ Health Behaviors at the Referees’ Football Training Centre in Baghdad City - Mohammed Hamzah Mahdi; Mohammed F. Khalifa (Institute of Medico-legal Publications Pvt Ltd, 2021)
Objective(s): The present study aims at evaluating third degree football referees’ Health behaviors at the Football Referee Training Centre in Baghdad City.Methodology: Quasi-experimental design, using one group test-retest approach, is carried throughout the present study for the period of October 25th 2019 through March 10th 2021.Non-probability, convenient sample of (40) third degree football referee while they are attending the Referees’ Football Training Centre for the purpose of training. All subjects who have agreed to participate in the study have signed consent form for maintenance of their confidentiality and ethical considerations. Self-report questionnaire is constructed out of the program for the purpose of the study. Such instrument is comprised of two parts; part I: Socio-demographic Information which include age, education, body mass index (BMI) and socioeconomic status (SES) and part II: Third Degree Football Referees’ Health Behaviors Scale that measures the third degree referees’ health behaviors. It is comprised of (4) sections that include body care and general health, smoking, drinking and drug use, psychosocial well-being and abusive behaviors. Content validity of the questionnaire is determined through panel of experts and test-retest reliability for equivalence is obtained throughout a pilot study.Results: Results of the study depict that third degree football referees have experienced positive health behaviors with respect to studied aspects. Further, there is no significant relationship between their health behaviors and the socio-demographic characteristics of age, education, body mass index and socioeconomic status.Conclusion: The study concludes that the third degree football referees’ health behaviors are improving as far as they are involved in the referees training center.